The Techniques of Upbringing Symbolism and Their Application in Public Communication - Aleksanyan, Anna (Journal of Sociology: Bulletin of Yerevan University, 2020)
From a communicative point of view, modern education is a social challenge due to social interaction based on communication influences that go beyond the modern education system. In the context of changes taking place in various modern social processes that affect the formation and development of a personality, the study, identification and application of the new potential of upbringing is of particular importance. The article presents the features of education in the formal and informal educational spheres. The article discusses the methodological basis for studying the upbringing process and considers the problem that the upbringing process takes place not only in the target education system, but also spontaneously, and can be controlled voluntarily and with unpredictable consequences. Based on this, the need to study the technique of visualization of education is revealed, and the question of observing various applications of the visualization of education, especially in the field of public communication, is raised.
Keywords: upbringing symbolism; visualization of upbringing; techniques of visualization; public communication